2021
DOI: 10.1055/a-1362-2243
|View full text |Cite
|
Sign up to set email alerts
|

Wie häufig werden Diagnosen aus dem Bereich der sexuellen Funktionsstörungen an deutschen Hochschulambulanzen für Psychotherapie an psychologischen Instituten vergeben?

Abstract: Zusammenfassung Einleitung Sexuelle Funktionsstörungen gelten als häufig. Gleichzeitig fehlen epidemiologische Daten zur Behandlungsprävalenz sexueller Funktionsstörungen in der ambulanten Psychotherapie. Im Rahmen eines Projekts zur Koordination der Datenerhebung an den deutschen Hochschulambulanzen für Psychotherapie wird erstmals eine Schätzung für dieses Behandlungssegment möglich. Forschungsziele Das Ziel dieser Studie ist die Darstellung der festgestellten F52-Diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
3
1
0
4
Order By: Relevance
“…Specificity, that is the probability of the DISEX‐F to identify true negatives was found to be excellent (at least 90%) for all DSM‐5 and ICD‐11 disorders. Therefore, results fully support the potential of the DISEX‐F to minimize rates of false negative DSM‐5 and ICD‐11 diagnoses, an important strength as previous studies have shown that sexual dysfunction often remains underdiagnosed in primary health care services (e.g., Heiden‐Rootes et al., 2017 ; Ribeiro et al., 2014 ) and outpatient clinics (e.g., Hoyer et al., 2009 ; Velten et al., 2021 ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Specificity, that is the probability of the DISEX‐F to identify true negatives was found to be excellent (at least 90%) for all DSM‐5 and ICD‐11 disorders. Therefore, results fully support the potential of the DISEX‐F to minimize rates of false negative DSM‐5 and ICD‐11 diagnoses, an important strength as previous studies have shown that sexual dysfunction often remains underdiagnosed in primary health care services (e.g., Heiden‐Rootes et al., 2017 ; Ribeiro et al., 2014 ) and outpatient clinics (e.g., Hoyer et al., 2009 ; Velten et al., 2021 ).…”
Section: Discussionsupporting
confidence: 64%
“…To explore whether ratings on the difficulty of the diagnostic decision depended on the classification system (DSM-5 vs. ICD-11), a two-tailed Wilcoxon signed rank test was conducted for which ratings of all diagnosticians (including the ratings from the videotapes; see Table 3 in Specificity, that is the probability of the DISEX-F to identify true negatives was found to be excellent (at least 90%) for all DSM-5 and ICD-11 disorders. Therefore, results fully support the potential of the DISEX-F to minimize rates of false negative DSM-5 and ICD-11 diagnoses, an important strength as previous studies have shown that sexual dysfunction often remains underdiagnosed in primary health care services (e.g., Heiden-Rootes et al, 2017;Ribeiro et al, 2014) and outpatient clinics (e.g., Hoyer et al, 2009;Velten et al, 2021).…”
Section: "Live" "Video"supporting
confidence: 67%
“…Consistent with these findings, a study of 4,504 patients from German university outpatient clinics for psychotherapy showed that general mental health care is underutilized by patients with sexual problems, with only 32 (0.7%) of patients treated in these clinics receiving a sexual dysfunction diagnosis [ 13 ]. Possible reasons for this underrepresentation of patients with sexual dysfunction in general clinical settings include the lack of appropriate diagnostic tools (e.g., structured interviews for sexual dysfunction) as well as shame and stigma associated with sexual problems.…”
Section: Introductionmentioning
confidence: 83%
“…Im Kontrast zu sowohl dem Belastungsgrad betroffener Frauen als auch zur Unsicherheit hinsichtlich adäquater diagnostischer Konzeptualisierung steht, dass das verfügbare Wissen zu den Entstehungsbedingungen als "eingeschränkt" (Bergeron et al 2015) oder "unklar" (APA 2013) bewertet wird. Dass diagnostische Unsicherheit aufseiten der Behandelnden weiterbesteht, lässt sich möglicherweise auch daran erkennen, dass sexuelle Funktionsstörungen in der klinischen Praxis deutlich seltener diagnostiziert werden, als Prävalenzzahlen nahelegen (Velten et al 2021) (Fonagy und Campbell 2015;Gilmore 2011). Im Einklang hiermit lassen auch die verfügbaren psychodynamischen Publikationen zu sexuellen Schmerzen und Schwierigkeiten beim Geschlechtsverkehr frühen Beziehungserfahrungen eine zentrale Rolle zukommen (Düring 1997;Hiller 1996;Richter-Appelt und Karg 2005).…”
Section: Dokumentationunclassified
“…Im Kontrast zu sowohl dem Belastungsgrad betroffener Frauen als auch zur Unsicherheit hinsichtlich adäquater diagnostischer Konzeptualisierung steht, dass das verfügbare Wissen zu den Entstehungsbedingungen als „eingeschränkt“ ( Bergeron et al 2015 ) oder „unklar“ ( APA 2013 ) bewertet wird. Dass diagnostische Unsicherheit aufseiten der Behandelnden weiterbesteht, lässt sich möglicherweise auch daran erkennen, dass sexuelle Funktionsstörungen in der klinischen Praxis deutlich seltener diagnostiziert werden, als Prävalenzzahlen nahelegen ( Velten et al 2021 ), wodurch Versorgungslücken zusätzlich vergrößert werden. In dem hier vorgestellten Promotionsprojekt hat sich die Autorin der Frage nach den Entstehungsbedingungen von sexuellen Schmerzphänomenen gewidmet, die vormals als Vaginismus und Dyspareunie bezeichnet wurden.…”
unclassified